Efficient Need Based Nitrogen Management in Rabi Maize (Zea mays L.) using Leaf Colour Chart Under Varied Planting Density - Naik, M. Ramesh; Hemalatha, S.; Reddy, A. P. K.; Madhuri, K. V. Naga; Umamahesh, V.; Rakesh, S. (International Journal of Bio-resource and Stress Management, 2022)
The field experiments were conducted for two consecutive rabi seasons (November –March) of 2017–18 and 2018–19 at the Wet land farm of S.V. Agricultural College, Tirupati to calibrate leaf colour chart (LCC) for increasing growth yield, nitrogen uptake under varied plant density to establish and evaluate threshold leaf colour greenness as a guide for in-season need based fertilizer N in maize. Research results indicated that the planting density, nitrogen levels and LCC threshold values significantly influenced all the growth and yield attributes, yield and nitrogen uptake. Plant height, days required to 50% tasselling and silking, cob yield, harvest index and nitrogen uptake increased significantly with increase in plant density i.e., 1,11,111 plants ha-1 with application of fertilizer nitrogen at higher dose i.e. 40 kg ha-1 and by using higher LCC threshold value (LCC 5) in different splits. Whereas, leaf area planr-1, cob girth, number of kernels rows cob-1 and number of kernels cob-1 was lessened significantly with increase in planting density, however it was increased with application of nitrogen at higher rate i.e.,40 kg ha-1 by using higher LCC threshold value (LCC 5) at various splits. Eventually, experimental results manifested that, fine-tuning of N dose and time of application by number of splits which synchronize the crop demand was the best management strategy for sustainable crop growth, production and productivity of maize.